From Financial Modelling To Financial Decision Intelligence: The Emerging Role Of Artificial Intelligence - Iman Sjamsu Rahardjo; Rida Justin Jacobalis; Ida Adhani; Bintoro Ariyanto; Oktovina Deci Rahakbauw (Jurnal Minfo Polgan, 2026)
Through the introduction of Financial Decision Intelligence, the study provides an integrative theoretical perspective explaining how Artificial Intelligence transforms financial decision-making into a continuous process of strategic intelligence creation. In doing so, it offers a conceptual foundation for future empirical research and advances the understanding of how organizations can leverage AI to strengthen strategic decision capability in the digital economy. Using an Integrative Literature Review (ILR), the study synthesizes multidisciplinary literature spanning strategic management, finance, business analytics, information systems, and artificial intelligence to develop an integrated theoretical framework. This study contributes to the strategic management literature by reconceptualizing financial modelling as a dynamic organizational capability, integrating previously fragmented theoretical perspectives, and establishing a conceptual foundation for future empirical research on AI-enabled financial decision capability. Beyond its theoretical contribution, the proposed framework also offers practical guidance for organizations seeking to strengthen evidence-based financial governance, strategic adaptability, and sustainable competitive advantage in increasingly data-intensive business environments.